Synthesis and evaluation of 4/5-hydroxy-2,3-diaryl(substituted)-cyclopent-2-en-1-ones as cis-restricted analogues of combretastatin A-4 as novel anticancer agents - Gurjar, Mukund K.; Wakharkar, Radhika D.; Singh, Anu T.; Jaggi, Manu; Borate, Hanumant B.; Shinde, Popat D.; Verma, Ritu; Rajendran, Praveen; Dutt, Sarjana; Singh, Gurvinder; Sanna, Vinod K.; Singh, Manoj K.; et al. (Journal of Medicinal Chemistry, 2007)
A new series of 2,3-diaryl-4/5-hydroxy-cyclopent-2-en-1-one analogues replacing the cis double bond of combretastatin A-4 (CA-4) by 4/5-hydroxy cyclopentenone moieties was designed and synthesized. The analogues displayed potent cytotoxic activity (IC50 < 1 mu g/mL) against a panel of human cancer cell lines and endothelial cells. The most potent analogues 11 and 42 belonging to the 5-hydroxy cyclopentenone class were further evaluated for their mechanism of action. Both of the analogues led to cell cycle arrest at G2/M phase and induced apoptosis in endothelial cells. Antitubulin property of 42 was superior to 11 and comparable to CA-4. The compound 42 had better aqueous solubility, metabolic stability, and pharmacokinetic profile than CA-4 and also demonstrated significant tumor regression in the human colon xenograft model. Our data suggests that cis-restricted analogues of CA-4 are a new class of molecules that have the potential to be developed as novel agents for the treatment of cancer.